Sposób kreowania opowieści przy użyciu opisów gestów rytualnych - Chruściak, Ilona (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, Pracownia Badań nad tradycją Oralną, 2017)
The paper discusses depictions of ritual gestures, both religious and everyday rituals as practised in oral poetry. Various elements of nonverbal communication were performed essentially in prayers, supplications and funeral rites. The above-mentioned gestures have been divided into three categories: gestures which emphasize the verbal message; gestures which complement the verbal message; gestures which contradict the verbal message. The analysis of references was conducted with the methodology of oral theory, semiotics and performance studies. It may be stated that the ritual gestures described by the oral poet structure the story of the Iliad and command the audience’s attention.
Keywords: Homer; Iliad; gesture; nonverbal communication; ritual; prayer; supplication; mourning